The Impression That I Get: The Influence of Brand Equity on Purchase Decisions - Musa, Muhammad Ichwan; Sareong, Wira Yunita; Haeruddin, M. Ikhwan Maulana; Haeruddin, Muhammad Ilham Wardhana; Burhanuddin, Burhanuddin (PINISI Discretion Review, 2022)
This study aims to determine the effect of brand equity on purchasing decisions in which there are four variables: (1) the effect of brand awareness on purchasing decisions at PT. Sarana Sinar Sulawesi (SSS) in South Sulawesi Province. (2) The influence of brand association of purchasing decisions at PT. Sarana Sinar Sulawesi in South Sulawesi Province. (3) The effect of perceived quality on purchasing decisions at PT. Sarana Sinar Sulawesi (SSS) in South Sulawesi Province. The population in this study were all consumers of PT. Sarana Sinar Sulawesi in 2017, while the sample taken was 100 respondents. The data analysis technique used was multiple regression analysis using two statistical method tests, namely partial test (t test) and simultaneous test (f test). The results of this study indicate that multiple regression analysis, the regression equation Y = 13.342 + 0.100X1 + 0.295X2 + 0.015X3 + 0.198X4 + 4.202 is obtained. Based on statistical data analysis, all variables are valid and reliable. In the classical assumption test, it is stated that all indicators are normally distributed and there is a significant linear relationship between each independent variable and the dependent variable. The coefficient of determination test results shows that 74% of purchasing decisions at PT. Sarana Sinar Sulawesi is influenced by the variables examined in this study.